2016
DOI: 10.1038/ncomms11365
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue mTORC2 regulates ChREBP-driven de novo lipogenesis and hepatic glucose metabolism

Abstract: Adipose tissue de novo lipogenesis (DNL) positively influences insulin sensitivity, is reduced in obesity, and predicts insulin resistance. Therefore, elucidating mechanisms controlling adipose tissue DNL could lead to therapies for type 2 diabetes. Here, we report that mechanistic target of rapamycin complex 2 (mTORC2) functions in white adipose tissue (WAT) to control expression of the lipogenic transcription factor ChREBPβ. Conditionally deleting the essential mTORC2 subunit Rictor in mature adipocytes decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
187
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(226 citation statements)
references
References 56 publications
31
187
1
3
Order By: Relevance
“…As previously reported (32)(33)(34), HFD-fed AdRiKO mice had an increased body size with no change in adiposity (Supplemental Figure 1, A-C; supplemental material available online with this article; https://doi.org/10.1172/JCI96139DS1). Furthermore, we confirmed that RICTOR expression, AKT (Ser473) phosphorylation, and PKC expression, readouts for mTORC2 signaling, were decreased, while S6K (Thr389) phosphorylation, a readout for mTORC1 signaling, was not affected in eWAT ( Figure 1B; see complete unedited blots in the supplemental material).…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…As previously reported (32)(33)(34), HFD-fed AdRiKO mice had an increased body size with no change in adiposity (Supplemental Figure 1, A-C; supplemental material available online with this article; https://doi.org/10.1172/JCI96139DS1). Furthermore, we confirmed that RICTOR expression, AKT (Ser473) phosphorylation, and PKC expression, readouts for mTORC2 signaling, were decreased, while S6K (Thr389) phosphorylation, a readout for mTORC1 signaling, was not affected in eWAT ( Figure 1B; see complete unedited blots in the supplemental material).…”
Section: Introductionsupporting
confidence: 78%
“…AdRiKO exacerbates systemic insulin resistance upon obesity, as evidenced by impaired glucose clearance in response to insulin treatment ( Figure 1A and refs. [32][33][34]. Thus, the AdRiKO mouse is a good model to investigate the causal relationship between insulin resistance and inflammation upon obesity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations